Outlook of the automotive e-commerce in the US & evaluation of a business idea - LowMiles - Sagols, Michael (2021)
This Bachelor’s thesis provides information about online used car retailers in the United States and provides insight on how to enter the market by providing e-commerce capabilities to traditional dealerships as a pre-seed venture. This thesis is divided into the theoretical section and the practical section. The theoretical section provides background on how to design a business model and business plan. It includes various strategic tools and frameworks. The practical section is where the business model and business plan described in the theoretical section are applied.